University: a universe of study and independent living opportunities for students with disabilities. Goals and critical issues - Pavone, Marisa; Bellacicco, Rosa (Education Sciences & Society - Open Access, 2016)
The study and inclusion experience of university students with disabilities is characterised by many complex issues but is also of great importance for personal, working and social life. Over the last two decades, international organisations have issued guidelines aimed at ensuring equal opportunities to underrepresented groups in higher education; first among them, the UN Convention on the Rights of Persons with Disabilities (2006)2. However, the academic quality of teaching programmes is greatly influenced by the autonomy of each university and by varying national legislations. Innovative trends move towards the model of inclusion: from the provision of services for a specific population to a structural reorganisation of the context. In Italy, the rate of students with disabilities at university has been found in quantitative and qualitative data since the early 1990s. Evidence shows that there has been a progressive increase in the number of enrolments leading in parallel to a more established provision of financial, professional and material resources. The few surveys conducted in the field, however, highlight the need to improve the quality of individualised courses and of the tools used, directing support towards a more systemic and diachronic perspective. Keywords higher education; disability; right to education; equal opportunities; inclusion; independent living